Blood Pressure Control Efforts in Hypertension Patients: An Exploratory Study - Rika Irma Rasmi; Basri Aramico; Maidar Maidar; Asnawi Abdullah; Fahmi Ichwansyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Non-communicable diseases (NCDs), especially hypertension, are the leading cause of premature death worldwide, with a high prevalence in low- and middle-income countries. In Indonesia, hypertension poses a major health challenge, particularly in coastal areas where diets are high in sodium. This study aims to explore the efforts made by individuals with hypertension in managing their blood pressure. A qualitative study with a case study approach was conducted in Kluet Selatan, South Aceh, in November 2024. Data were collected through in-depth interviews and focus group discussions (FGDs) involving 12 participants, including hypertension patients, family members, health workers, and community leaders. Data were recorded, transcribed verbatim, and analyzed using thematic analysis to identify patterns and key themes related to hypertension management. The results revealed that patients had initiated dietary changes, increased physical activity, and practiced stress management. However, they encountered challenges such as financial limitations, ingrained eating habits, and restricted access to health facilities. Family involvement and the use of traditional remedies were found to support hypertension control. Despite these efforts, persistent social, cultural, and economic barriers hinder sustainable behavior change. Limited health education and lack of access to specialized care also affect long-term hypertension management in this setting.